To apply the distributive property, we will multiply each term inside the parentheses by the number outside the parentheses.
First, let's apply the distributive property to 2(a + 5):
2(a + 5) = 2 * a + 2 * 5
= 2a + 10
Next, let's apply the distributive property to 4(2a + 3):
4(2a + 3) = 4 * 2a + 4 * 3
= 8a + 12
Now, let's combine like terms:
2(a + 5) + 4(2a + 3) - 10
= 2a + 10 + 8a + 12 - 10
Finally, let's combine the constants:
2a + 10 + 8a + 12 - 10
= (2a + 8a) + (10 + 12 - 10)
= 10a + 12
Apply the distributive property and combine like terms to generate an expression equivalent to 2(a + 5) + 4 (2a + 3) - 10
1 answer